Usefulness of noninvasive shear wave elastography for the assessment of hepatic fibrosis in dogs with hepatic disease. (28th August 2019) - Tamura, Masahiro; Ohta, Hiroshi; Shimbo, Genya; Osuga, Tatsuyuki; Sasaki, Noboru; Morishita, Keitaro; Kagawa, Yumiko; Takiguchi, Mitsuyoshi
Abstract: Background: Two‐dimensional shear wave elastography (2D‐SWE) can noninvasively evaluate hepatic elastic modulus as shear wave velocity (SWV). Additionally, it may predict the presence of clinical relevant hepatic fibrosis (≥F2) in dogs with hepatic disease. Objectives: To investigate whether SWV measured by 2D‐SWE can differentiate between dogs with (≥F2) and without (F0‐1) clinically relevant hepatic fibrosis. Animals: Twenty‐eight client‐owned dogs with hepatic disease and 8 normal healthy Beagle dogs were enrolled. Methods: In this cross‐sectional prospective study, SWVs were measured using 2D‐SWE in all dogs. Hepatic fibrosis stages and necroinflammatory activity grades were histopathologically evaluated using a histological scoring scheme that was adapted from the Ishak schema used in human medicine. Results: Median SWVs were significantly higher in dogs with clinically relevant hepatic fibrosis (2.04 m/s; range, 1.81‐2.26 m/s) than in healthy dogs (1.51 m/s; range, 1.44‐1.66 m/s; P = .007), and dogs without clinically relevant hepatic fibrosis (1.56 m/s; range, 1.37‐1.67 m/s; P  < .001). However, no significant difference was found in the SWVs between dogs without clinically relevant hepatic fibrosis and healthy dogs ( P = .99). Furthermore, median SWVs were not significantly different among dogs with necroinflammatory activity, those without necroinflammatory activity, and healthy dogs (Kruskal‐Wallis test, P = .12). Conclusions and Clinical Importance: The 2D‐SWE may be useful for predicting the presence of hepatic fibrosis in dogs with hepatic disease.